2019
DOI: 10.1142/s1088424619300076
|View full text |Cite
|
Sign up to set email alerts
|

How protoporphyrinogen IX oxidase inhibitors and transgenesis contribute to elucidate plant tetrapyrrole pathway

Abstract: Several families of herbicides, especially diphenyl ether (DPE) and pyrimidinedione, target the plant tetrapyrrole biosynthesis pathways and in particular one key enzyme, protoporphyrinogen IX oxidase (PPO). When plants are treated with DPE or pyrimidinedione, an accumulation of protoporphyrin IX, the first photosensitizer of this pathway, is observed in cytosol where it becomes very deleterious under light. Indeed these herbicides trigger plant death in two distinct ways: (i) inhibition of chlorophylls and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Previous study indicated that the increasing accumulation of saturated fatty acids in the early senescence stage could improve the sensitivity to ethylene and promote the owering of Petunia hybrida [29]. And long-chain fatty acids were involved in the transport of polar auxin in A. thaliana [21]. In addition, studies on membrane lipids of photosynthetic organs in leaves showed that the increase of unsaturated fatty acid ratio helps to protect plant PSII damage under stress, maintain the stability of thylakoid membrane, and improve the photosynthetic heat resistance of plants.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous study indicated that the increasing accumulation of saturated fatty acids in the early senescence stage could improve the sensitivity to ethylene and promote the owering of Petunia hybrida [29]. And long-chain fatty acids were involved in the transport of polar auxin in A. thaliana [21]. In addition, studies on membrane lipids of photosynthetic organs in leaves showed that the increase of unsaturated fatty acid ratio helps to protect plant PSII damage under stress, maintain the stability of thylakoid membrane, and improve the photosynthetic heat resistance of plants.…”
Section: Discussionmentioning
confidence: 98%
“…However, the transcription level of AdhemH was up-regulated in BT plants. The hemH catalyzes the chelation of protoporphyrin IX with Fe to form heme, which essentially competes with chlorophyll synthesis pathway for protoporphyrin IX [21]. In cucumber seedlings under salt stress, the transcription level of protoporphyrin iron chelatase increased, while the transcription level of several genes in chlorophyll synthesis pathway was down-regulated.…”
Section: Discussionmentioning
confidence: 99%
“…PPO-inhibiting herbicides target the biosynthesis of critical pigments in living plants. They can inactivate the PPO enzyme via competing for the binding site between the protogen and PPO enzyme . The inhibition of the PPO enzyme leads to a block in the biosynthesis of proto and causes the accumulation and leakage of protogen into the cytoplasm.…”
Section: Synthetic Carboxylic Acids and Their Derivatives For Herbici...mentioning
confidence: 99%
“…To fight off plant competitors and pathogens, new approaches are necessary for safe practices in agriculture such as genetically modified plants, genetic improvements, as well as organic and integrated agriculture 5 , 6 . The photodynamic treatment is a general and new concept with a large spectrum of applications for animal and plant cells, plant and animal pathogens, as well as microorganisms 7 18 . Thus, photodynamic treatment could represent an innovative and powerful strategy to fight off plant competitors and pathogens in future agricultural practices 17 .…”
Section: Introductionmentioning
confidence: 99%